The Effect of 0.2% Sodium Fluoride Mouthwash in Prevention of Dental Caries According to the DMFT Index - Esrafil Balaei; Nasser Asl Aminabadi; Firoz Pouralibaba (Tabriz University of Medical Sciences, 2007)
Background and aims. Dental caries still remains a major problem in the field of oral and dental health and its prevention is more important than its treatment. Fluoride plays a significant role in prevention of caries, and improving oral and dental health. One of the common ways of fluoride use is the use of a fluoride-containing mouthwash, the most important of which in use is 0.2% sodium fluoride mouthwash. School-based fluoride mouthwash programs have been used for delivering oral and dental health to children in recent years. The aim of the present study was to assess the efficiency of 0.2% sodium fluoride mouthwash in prevention of dental caries according to DMFT index. Material and methods. The study included a case and a control group. For each group, 100 students were selected randomly from elementary schools of Tabriz, Iran. Case group had been participating in school-based fluoride mouthwash program for three years, while control group did not benefit from the program. The two groups were assessed by means of intra-oral examination. Data was recorded using DMFT index. Results. Following the use of 0.2% sodium fluoride mouthwash, mean DMFT index in case group decreased as much as 51.5% compared to that of control group. The mean values of decrease for the decayed, missing and filled indices were 45%, 44% and 59%, respectively. The decrease in DMFT value of the case group compared to that of control group was statistically significant (p< 0.001). A statistically significant decrease was seen in the decayed and filled indices of case group (p=0.042 and p=0.016, respectively), however the missing index did not show any statistically significant difference between the two groups (p=0.361). Conclusion. According to this study results, the weekly use of 0.2% sodium fluoride mouthwash program has been successful in elementary schools of Tabriz. Such program can play an important role in the improvement of oral and dental health among children of school age.